Numerically efficient analysis of FRP confined CFST members under lateral low-velocity impact loading - Tang, Jikai; Liu, Bin; Kang, Lijing; Fan, Wei; Zhao, Debo; Wang, Tao; He, Liang; Xie, Jing (Frontiers in Materials, 2024)
Fiber-reinforced polymer (FRP) confined concrete filled steel tube (CFST) structures effectively harness the advantages of FRP materials, improving the performance of CFST structures and overcoming durability issues of steel tubes. Three-dimensional detailed finite element (FE) models are usually employed to estimate the impact-resistant performance of FRP confined CFST members under impact loadings. However, detailed FE models are typically complex in modeling and low in calculation efficiency as well as require high performance in computer hardware. Hence, this paper aims to develop an alternative modeling method that can predict the impact behavior of FRP confined CFST members with high efficiency and low requirements in computer resources. The proposed method includes a contact model using mass-spring-damper elements to describe the contact behavior between the impactor and the impacted FRP confined CFST members and a nonlinear fiber-based beam-column element model to simulate the behavior of FRP-confined CFST members under impact loading. The accuracies of fiber-section beam-column elements are carefully examined for FRP confined CFST members based on quasi-static test data reported in the literature.It is found that the fiber-based elements considering confinement effects provided by FRP and steel tubes can accurately predict the force-deformation relationship of the FRP confined CFST members under monotonic loading. By incorporating the strain-rate effects of concrete, steel, and FRP materials, the validated fiber-section elements are employed to simulate eight impact tests on FRP confined CFST members. Good agreements are observed between the results obtained from the proposed models and the experimental data. The computational efficiency of the developed model is three orders of magnitude faster than that of the conventional detailed FE model.